Issuance of Land Legality By The Batam Concession Agency Against Complete Systematic Land Registration Program Certificates Issued In Batam - Eling Eling; Benny Djaja (PT Publikasiku Academic Solution, 2023)
Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning Complete Systematic Land Registration (PTSL) was made to ensure legal certainty and legal protection of land rights owned by the community fairly and equitably, but unfortunately, it contradicts with the Regulation of the Head of the Batam Free Trade Zone and Free Port Concession Agency Number 27 of 2017 concerning Implementation of Land Allocation. The purpose of this study is to analyze what regulations must be used by people who want to apply for land permits in Batam and how to obtain land permits in Batam. This study used normative legal research or doctrinal research which refers to positive legal norms governing the Issuance of Land Legality by the Batam Concession Agency Against Complete Systematic Land Registration Program Certificates Issued in Batam. The results of this study that the regulations used are still regulations issued by the Head of the Batam Free Trade Zone and Free Port Concession Agency Number 27 of 2017 concerning the Implementation of Land Allocation. Because Batam is one of the regions in Indonesia with regional autonomy rights.